Student's professional competence development using the blended learning - Sumihar Simangunsong (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
This research is motivated by the low level of competence of graduates from universities which results in low professionalism in the world of work in the current era of globalization. The purpose of this research is to show the relationship of increasing professional competence through blended learning model. The sample of this study was forty-five students majoring in Mining ISTP FY 2021/2022 who were made into two sample groups. The control group (CG) of 20 students was the group that was not treated with the blended learning model, while the experimental group (EG) of 25 students was treated with the blended learning model. This research was conducted using a quantitative descriptive method. To determine the level of professional competence of students, a test is used for each competency criterion. The results obtained at the level of competence in the cognitive control group 0%, andragogical competence 25% and social competence 35%, and in the experimental group cognitive 48%, andragogical competence 72% and social competence 64%. The results of this study concluded that the blended learning model can improve and develop the professional competence of graduate students so that they are competent in the world of work in the era of globalization.